Paradigma Syariat Islam dalam Kerangka Otonomi Khusus (Studi Kajian di Provinsi Aceh) - Abdul Gani Isa (Media Syari'ah, 2012)
The appearance of Islamic law implementation demand in public domain in Indonesia has its root since the formation era of Republic Indonesia after independence. However, this issue became more important after reformation era, especially after the fall of new order regime and enactment of Law No. 22/1999 on Regional/Provincial Government. Meanwhile, the implementation of Islamic law in Aceh has its own legality and legitimacy in the framework of Indonesian law state and in line of its constitution. This grant of acknowledgment to implement sharia law for Aceh based on Law No.44/1999 on Special Status of Aceh Province and Law No. 11/2006 on Aceh Government. Legally based on both law, some provincial regulations have been enacted to speed up the implementation of sharia law in Aceh.